Analysis of SMEs in Bulgaria – Assessment of Their Innovation Activities (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The main thesis of the report is that the vast choice of planned innovation is given by combining traditional financial and economic assessment approaches innovation, namely through the net present value (NPV). The aim is to analyze the situation of SMEs in Bulgaria, to identify the problems facing their development and to formulate recommendations to address them.